2014
DOI: 10.1111/all.12443
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic evaluation of well‐characterized allergy to staple foods in adults

Abstract: Swedish adults with allergy to staple foods have higher total costs determined as direct, indirect, and intangible costs using the disease-specific socioeconomic questionnaire. Thus, total costs were 8164 € higher per year in households with at least one adult allergic to staple foods compared with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 31 publications
0
33
0
1
Order By: Relevance
“…Intangible costs were also higher in households with one food allergic adult, compared with controls. 8 We now extend this work to households with children and adolescents. The objective of this study was to estimate the direct, indirect, and intangible costs of food allergy in households with a child or adolescent with objectively diagnosed allergy to the staple foods such as cow's milk, hen's egg, and/or wheat, and to compare these costs with age-and sex-matched controls.…”
Section: Abbreviations Usedmentioning
confidence: 98%
See 2 more Smart Citations
“…Intangible costs were also higher in households with one food allergic adult, compared with controls. 8 We now extend this work to households with children and adolescents. The objective of this study was to estimate the direct, indirect, and intangible costs of food allergy in households with a child or adolescent with objectively diagnosed allergy to the staple foods such as cow's milk, hen's egg, and/or wheat, and to compare these costs with age-and sex-matched controls.…”
Section: Abbreviations Usedmentioning
confidence: 98%
“…7 Although difficult to assess monetarily, these costs are estimated to be high. 7,8 On the basis of an algorithm to estimate costs of immunoglobulin E (IgE)-mediated food allergy to society, 7 we recently identified that the total annual costs for households with one food allergic adult were V8164 higher than those for age-and sex-matched controls. 8 Notably, the driving factor was indirect, rather than direct, costs.…”
Section: Abbreviations Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Šiuolaikinėje alergologijos literatūroje daug dėmesio skiriama alergijai maistui [1][2][3][4][5]. Paskelbti padidėjusio jautrumo maistui klausimynų pirmieji rezultatai [6].…”
Section: įVadasunclassified
“…Socio-economic status (SES) also can affect allergic disorders, as studied in affluent countries [16][17][18]. However, there are not many studies addressing the pattern of allergic disorders within an urban centre in a developing country where large differences in SES and lifestyle are seen.…”
Section: Introductionmentioning
confidence: 99%